Molecular and cytological characterization of the global Musa germplasm collection provides insights into the treasure of banana diversity - Christelova, P.; Langhe, E. de; Hribova, E.; Cizkova, J.; Sardos, J.; Husakova, M.; Houwe, Ines van den; Sutanto, A.; Kepler, A.K.; Swennen, Rony L.; Roux, N.; Doležel, Jaroslav (Springer, 2017)
Bananas (Musa spp.) are one of the main fruit crops grown worldwide. With the annual production reaching 144 million tons, their production represents an important contribution to the economies of many countries in Asia, Africa, Latin-America and Pacific Islands. Most importantly, bananas are a staple food for millions of people living in the tropics. Unfortunately, sustainable banana production is endangered by various diseases and pests, and the breeding for resistant cultivars relies on a far too small base of genetic variation. Greater diversity needs to be incorporated in breeding, especially of wild species. Such work requires a large and thoroughly characterized germplasm collection, which also is a safe depository of genetic diversity. The largest ex situ Musa germplasm collection is kept at the International Transit Centre (ITC) in Leuven (Belgium) and currently comprises over 1500 accessions. This report summarizes the results of systematic cytological and molecular characterization of the Musa ITC collection. By December 2015, 630 accessions have been genotyped. The SSR markers confirmed the previous morphological based classification for 84% of ITC accessions analyzed. The remaining 16% of the genotyped entries may need field verification by taxonomist to decide if the unexpected classification by SSR genotyping was correct. The ploidy level estimation complements the molecular data. The genotyping continues for the entire ITC collection, including newly introduced accessions, to assure that the genotype of each accession is known in the largest global Musa gene bank.